Study on the control targets and measures for total diesel consumption from mobile sources in Beijing, China - Ai, Yi; Cui, Yangyang; Ge, Yunshan; Wu, Xuefang; Wu, Tongran; Liu, Xinyu; Shen, Yan; Liu, Mingyu; Wan, Yunfei; Yi, Huawei; Xue, Yifeng (Frontiers in Environmental Science, 2022)
Based on the current air pollution control and CO2 emission reduction policies, this study analyzes the energy structure, number of motor vehicles and non-road mobile machinery, energy consumption and pollutant emissions in Beijing. Meanwhile, the diesel consumption characteristics and problems facing emission reduction in key fields were investigated, such as medium- and heavy-duty diesel trucks, long-distance passenger and tourist diesel vehicles, and non-road machinery, which are areas with difficult-to-reduce diesel consumption, and the control targets and measures for total diesel consumption was proposed. As a result, the higher diesel consumption per unit area in Beijing is related to the more large passenger cars and freight trucks population. In recent decade, the number of diesel vehicles has increased, the vehicle type structure has been optimized, the proportion of vehicles with high emission standards has increased, and the absolute pollutant emissions have decreased. Moreover, medium and large passenger vehicles, medium and heavy trucks and construction machinery are the main contributors of diesel consumption. These vehicle types are also difficult for emission control and reduction, and their replacement of new-energy vehicles are relatively limit. The main control measures for diesel consumption are as follows. Firstly, a green transportation mode can be adopted for the goods that can be converted from roads to railways. Secondly, fuel consumption reduction for nonroad mobile machinery can be realized by tightening fuel consumption limits, setting appropriate maximum retirement life, establishing low or ultra low-emission zones, and establishing demonstration plot for electric vehicle (EV) substitution for mobile machinery. To improve the air quality and take the lead in carbon neutrality in the future, Beijing must further accelerate the energy structure adjustment and the development of new-energy vehicles in the transportation sector. Carbon neutralization is an important opportunity for diesel consumption reduction, and the synergistic control of atmospheric pollution and carbon emissions from diesel combustion must be strengthened.